PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - RACHMATUS SOLIKHAH, DESY; , HARIYATI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the influence of Enterprise Risk Management (ERM) disclosure on firm value with profitability as a mediating variable. Samples of this study are being chosen by using purposive sampling method and obtained from 86 companies included in Kompas 100, Bisnis 27, LQ45, and IDX 30 indexes and listed on Indonesia Stock Exchange. Data collection techniques used this study are documentation. To analyze the data, this study uses analysis of Structural Equation Model (SEM) approach Partial Least Square (PLS). In data processing using software WarpPLS 5.0. The result showed that ERM disclosure has a positive effect on firm value. However, profitability in this study was not able to mediated relationship between ERM disclosure on firm value. Keywords : Enterprise Risk Management Disclosure, Firm Value, Profitability